Following Foucault The Trail of the Fox - Richards, Howard (African Sun Media, 2018)
[This book] "... offers prospective readers the opportunity to assess the respective merits of a poststructuralist, archaeological/genealogical approach (Foucault's) and that of a neo-pragmatist, hyper-Popperian, problem-solving critical realist, Howard Richards, who values the fact that Foucault was sensitive to the need to defend and empower 'subjugated knowledges'." - Bert Olivier, University of the Free State